2014
DOI: 10.1083/jcb.201402128
|View full text |Cite
|
Sign up to set email alerts
|

Hrr25 triggers selective autophagy–related pathways by phosphorylating receptor proteins

Abstract: The budding yeast kinase Hrr25 regulates two selective autophagy–related pathways by phosphorylating degradation target receptors and thereby promoting their interaction with Atg11 and the formation of autophagosomal membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 54 publications
4
113
0
1
Order By: Relevance
“…The middle band, which was insensitive to Hrr25 depletion, may indicate Atg34 phosphorylation by another kinase. Alternatively, the band might reflect incomplete depletion of Hrr25; consistent with this idea, hrr25-aid cells continued to grow at a slow rate even in the presence of IAA [17]. We also performed in vitro phosphorylation reactions using recombinant Atg34 and Hrr25, which were expressed in and purified from E. coli cells.…”
Section: Hrr25 Phosphorylates Atg34 Under Nitrogen-starvation Conditionsmentioning
confidence: 82%
See 1 more Smart Citation
“…The middle band, which was insensitive to Hrr25 depletion, may indicate Atg34 phosphorylation by another kinase. Alternatively, the band might reflect incomplete depletion of Hrr25; consistent with this idea, hrr25-aid cells continued to grow at a slow rate even in the presence of IAA [17]. We also performed in vitro phosphorylation reactions using recombinant Atg34 and Hrr25, which were expressed in and purified from E. coli cells.…”
Section: Hrr25 Phosphorylates Atg34 Under Nitrogen-starvation Conditionsmentioning
confidence: 82%
“…Escherichia coli BL21 cells harboring pGEX-6P-Atg34 (donated by Dr. Nobuo Noda), -Hrr25, or Hrr25 K38A [17], or the pGEX-6P-1 (empty) vector, were cultured at 37°C in LB media (10 mg/ ml tryptone, 5 mg/ml yeast extract, 10 mg/ml NaCl, and 1 mM NaOH) containing 50 lg/ml ampicillin. To induce protein expression, isopropyl b-D-thiogalactopyranoside was added to a final concentration of 0.1 mM.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Interestingly, Hrr25 is also involved in many other cellular processes, including autophagy (Tanaka et al, 2014), trafficking through the Golgi (Lord et al, 2011), DNA damage repair (Hoekstra et al, 1991) and mitotic spindle function (Peng et al, 2015b;Petronczki et al, 2006). Whether Hrr25 coordinates any of these activities with CME needs to be determined.…”
Section: Phosphoregulationmentioning
confidence: 99%
“…Several of the Atg proteins are phosphorylated, but until recently it was not known if any of these proteins were Atg1 substrates. Many other protein kinases (i.e., proteins that are not part of the autophagy core machinery) also modulate autophagy activity, [25][26][27][28] but in most cases the relevant targets have not been identified. Atg9 plays a key role in autophagy, and we recently demonstrated that the amount of the Atg9 protein correlates with the rate of autophagosome formation.…”
Section: Determination Of Atg9 Phosphorylation Sitesmentioning
confidence: 99%